2020
DOI: 10.1098/rsos.201602
|View full text |Cite
|
Sign up to set email alerts
|

Learned valuation during forage decision-making in cuttlefish

Abstract: Decision-making, when humans and other animals choose between two options, is not always based on the absolute values of the options but can also depend on their relative values. The present study examines whether decision-making by cuttlefish is dependent on relative values learned from previous experience. Cuttlefish preferred a larger quantity when making a choice between one or two shrimps (1 versus 2) during a two-alternative forced choice. However, after cuttlefish were primed under conditions where they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…In cuttlefish, we have shown that when animals make a decision between one large shrimp and two small shrimps, this depends on their appetite state; that is, they prefer a single larger shrimp when they are starving, but two smaller shrimps when they are satiated 43 . In a separate study, we have also shown that foraging decision-making by cuttlefish is dependent on the relative values learned from previous experience 44 . Cuttlefish typically preferred the larger quantity in the one vs. two shrimp test.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…In cuttlefish, we have shown that when animals make a decision between one large shrimp and two small shrimps, this depends on their appetite state; that is, they prefer a single larger shrimp when they are starving, but two smaller shrimps when they are satiated 43 . In a separate study, we have also shown that foraging decision-making by cuttlefish is dependent on the relative values learned from previous experience 44 . Cuttlefish typically preferred the larger quantity in the one vs. two shrimp test.…”
Section: Introductionmentioning
confidence: 83%
“…This suggests that cuttlefish are making foraging decisions based on a state-dependent valuation 43 . Yet in another study, it has also been shown that forage decision making by cuttlefish is dependent on relative values learned during previous experiences 44 . In the present study, we demonstrate that the unexpected reward was able to affect risk assessment by cuttlefish and this consequently changes their foraging strategy.…”
Section: Discussionmentioning
confidence: 99%
“…In cuttlefish, the capacity to delay gratification might have evolved in response to different ecological pressures, such as the need to optimize foraging behaviour [47]. In the wild, cuttlefish have long rest periods where they remain stationary and camouflaged for the majority of the time [71].…”
Section: Discussionmentioning
confidence: 99%
“…predators learning to stalk prey) [78]. Furthermore, diverse taxa such as great tits (Parus major) [79], bluegill sunfish (Lepomis macrochirus) [80], shore crabs (Carcinus maenas) [81] and pharaoh cuttlefish (Sepia pharaonis) [47], can learn to reject low-value prey when high-value prey are abundant. Such patterns have been argued to reflect associative learning because theoretically behavioural patterns of self-control can develop through conditioned reinforcement learning [82].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation